Towards evidence-based software engineering research in Malaysia - Salleh, Norsaremah (2012)
Evidence-based research has been matured and established in many other disciplines such as in Medicine and Psychology. One of the methods that have been employed widely to support evidence-based practices is the Systematic Literature Review (SLR) method. It is a review method that aims to provide unbiased or fair evaluation to existing research evidence. The aim of this study is to survey possible use of the SLR methodology to support software engineering research in Malaysia. Based on a survey conducted during an SLR workshop in UNITEN, we found that most of the participants valued SLR as an important method to be used for conducting a literature review. Hence, we believe that knowledge about using SLR should be propagated to encourage more researchers to apply it in their research.